2020
DOI: 10.3389/fgene.2020.579411
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Transmission of a Hyper-Virulent Meningococcal Clone Due to High Effective Contact Numbers and Super Spreaders

Abstract: Rapid transmission, a critical contributory factor in outbreaks of invasive meningococcal disease, requires naïve populations of sufficient size and intermingling. We examined genomic variability and transmission dynamics in a student population subject to an 11-fold increase in carriage of a hypervirulent Neisseria meningitidis serogroup W ST-11 clone. Phylogenetic clusters, mutation and recombination rates were derived by bioinformatic analyses of whole-genome sequencing data. Transmission dynamics were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It should, however, be taken into account that this study investigated a close-contact and thus high-risk setting. Also, a recent modeling study using the same carriage data showed that vaccination led to a carriage plateau, and the authors predicted that a higher coverage rate would have produced further reduction in carriage levels [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should, however, be taken into account that this study investigated a close-contact and thus high-risk setting. Also, a recent modeling study using the same carriage data showed that vaccination led to a carriage plateau, and the authors predicted that a higher coverage rate would have produced further reduction in carriage levels [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…meningitidis isolates may arise from the higher rates of recombination and phase variation in the meningococcal genome [ 29 ], or from a prolonged divergence time if the N . meningitidis strain spreads among asymptomatic carriers prior to the outbreak [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks involving other bacterial pathogens often exhibit fewer differences among isolates (24 SNPs for Staphylococcus aureus [28], 7 cgMLST alleles for Listeria monocytogenes [14]). The greater divergence among N. meningitidis isolates may arise from the higher rates of recombination and phase variation in the meningococcal genome [29], or from a prolonged divergence time if the N. meningitidis strain spreads among asymptomatic carriers prior to the outbreak [8].…”
Section: Plos Pathogensmentioning
confidence: 99%
See 2 more Smart Citations